Desarrollo de nanocompuestos de plata como agentes desinfectantes in-vitro (2020)
The present work evaluates the application of silver nanostructured compounds (AgNCs) as bactericidal agents. The trials were carried out on two strains of bacteria, one Gram Negative and another Gram Positive as a reference, Escherichia coli and Staphylococcus aureus respectively. The synthesized nanocomposite used iron nanoparticles (NPIO) as substrate, coated by iron oxide (Fe3O4 - NPIO). In order to control subsequent oxidation processes, as well as increase the surface area and biocompatibility of the nanoparticles, the NPIOs were coated with a silicon oxide precursor sun (SiO2), to finally decorate them with silver nanoparticles (AgNPs). NPIOs were produced by a coprecipiation process, as were AgNPs. The SiO2 sun was synthesized by ultrasound-assisted sol-gel methodology. Trials to determine the minimum biocide dose (DMB) were advanced in-vitro. The DMB tests showed that all synthesized AgNCs exhibited bacteriostatic and bactericidal behavior, according to the dose of AgNPs used, this being a viable alternative for the disinfection of materials contaminated with pathogenic microorganisms, friendly to the environment, since the AgNCs have paramagnetic properties and can be recovered by interaction with an electromagnetic field.